Unexplained mysteries of World War II - Harwood, Jeremy (the History Press, 2014)
"Strange happenings, unsolved riddles, secret alliances, attempted cover-ups, and plots and conspiracies - Unexplained Mysteries of World War II sheds new light on undoubtedly the most important period of 20th-century history. Superbly illustrated and with spectacular contemporary photographs,and whilst painstakingly researched, this is history without the boring bits and will enthral the reader."--Publisher's description